FERTILITY DISORDERS IN PRIMARY CILIARY DYSKINESIA: MECHANISMS, DIAGNOSTICS AND MANAGEMENT OPTIONS - Irmina Czerepak; Marcin Kapij; Michał Ziemba; Klaudia Zackiewicz; Agata Wińska; Agata Ogórek; Miłosz Rudziński; Maria Wojnowska; Paweł Liszka; Julianna Zielska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Primary ciliary dyskinesia (PCD) is a rare genetic disorder of motile cilia affecting both respiratory and reproductive systems. Because ciliary motility is essential for sperm propulsion and gamete transport in the female reproductive tract, individuals with PCD frequently present with subfertility or infertility. The purpose of this review is to synthesize current knowledge on mechanisms, clinical presentation, diagnostic pathways, and management of fertility disorders in PCD. Description of the state of knowledge: Evidence from narrative reviews and recent cohort studies indicates that fertility impairment is more common in men than in women, with subfertility reported in up to 83% of men and 61% of women. A large cross-sectional study found infertility in 78% of men and 61% of women attempting conception and documented an increased rate of ectopic pregnancy (7.6% of pregnancies). In men, infertility is mainly due to immotile or severely dysmotile sperm resulting from axonemal defects, although many sperm remain viable; some genotypes also present with oligozoospermia, MMAF or sperm DNA damage. In women, impaired ciliary motility in the fallopian tubes and endometrium contributes to delayed embryo transport and increased ectopic pregnancy risk. Diagnosis relies on specialized PCD testing (nNO, HSVM, TEM, genetic analysis), combined with standard infertility evaluation. Assisted reproductive technologies—especially ICSI with vitality-based sperm selection—are highly effective for male PCD-related infertility, while IVF/ICSI provides favorable outcomes in women, although early pregnancy ultrasound is recommended. Summary: Fertility disorders are a significant but manageable aspect of primary ciliary dyskinesia. A substantial proportion of affected individuals can achieve pregnancy, often with the support of ART. Early recognition of PCD in infertile patients, multidisciplinary management, and attention to genotype–phenotype correlations improve counselling and treatment planning. Further prospective studies are needed to refine prognostic predictions and optimize reproductive care in PCD.